Performance, Growth Curves and Carcass Yield of Four Strains of Broiler Chicken - Nogueira, B. R. F. [UNESP]; Reis, M. P. [UNESP]; Carvalho, A. C.; Mendoza, E. A. C.; Oliveira, B. L.; Silva, V. A.; Bertechini, A. G. (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2019)
The objective of this study was to evaluate the performance, carcass yield and growth curves of different commercial strains of broiler chicken. 2400 day-old chicks, males and females of the Cobb500, RossAp95, Hubbard Flex and a new Francesa line were used. The birds were distributed in a completely randomized design in a factorial arrangement 4x2 (line x sex), forming eight treatments with 10 replicates each. The birds were fed with the same diet. Feed intake, weight gain and feed conversion were determined. At 42 days, it was determined at the request of carcass and cuts of each lineage. The Gompertz model was applied to a growth curve for each line. The RossAP95 line shows the best performance results. Growth curves showed lower sexual dimorphism in the Hubbard Flex line. The Hubbard Flex strain presented higher thigh yield and a Cobb500 genetics the higher breast yield. Based on the results found it was observed that the RossAP95 performed better. Hubbard Flex line exhibits the least sexual dimorphism. The Cobb500 have better yield for breast and as Hubbard Flex birds greater thigh yield.
Keywords: Broiler chicken genetics; gompertz; viscera yield